Living Work Ethics of Muslim Entrepreneurs in Tasikmalaya City, Indonesia - Rifki Rosyad; Dede Aji Mardani; Wan Zailan Kamaruddin Wan Ali (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
This study aimed to analyze Muslim entrepreneurs' work ethic who can directly contribute to the City's economic growth where they live, namely Tasikmalaya City of West Java of Indonesia. The City is a religious city, so its residents, including business people, base their lives on Islam. Numerous Islamic education institutions are enormous and continue to increase yearly; it is also characterized by regional regulations that impose Islamic law in the City. This study used a qualitative method with an anthropological approach. This approach was necessary because this work ethic was related to specific human activities. This study found that Muslim entrepreneurs' work ethic in Tasikmalaya city could be categorized as high by adhering to honesty, discipline, respect for time, working sincerely, adhering to procedures, and submitting reports on time. Besides, hard work was also an essential ethos for work success. However, hard work here also means worship. Based on the principle of monotheism, work is an investment and buying and selling with God, namely by always giving charity as savings for heaven. This study confirmed the linkage between religion and work ethic found by Max Weber and its correlation to the Muslim community in the religious city of Tasikmalaya. This study explores the work behavior of Muslim traders and their employees to encourage integrity, a sense of responsibility, quality, self-discipline, and teamwork in job releases that determine whether a strong work ethic or a weak work ethic contributes to the level of performance.